DEVELOPMENT OF ONLINE BANKING IN THE REPUBLIC OF UZBEKISTAN - Oybekovna, Shermamatova Iroda (Antis Publisher, 2024)
This article explores the development of online banking in the Republic of Uzbekistan, highlighting its significant impact on the modernization of the banking sector and the enhancement of financial inclusion. The article discusses the key drivers behind the adoption of online banking, including consumer demand and the proliferation of mobile technologies. Furthermore, it examines the role of private and state-owned banks in expanding digital banking services and their efforts to educate and protect users